Provider perceptions of availability, accessibility, and adequacy of health and behavioral services for Latino immigrants in Philadelphia: a qualitative study - Ana P. Martinez-Donate; Nishita Dsouza; Sierra Cuellar; Gabrielle Connor; Claudia Zumaeta-Castillo; Mariana Lazo-Elizondo; Yoshiaki Yamasaki; Cristina Perez; Amy Carroll-Scott; Omar Martinez; Elizabeth McGhee Hassrick (BMC, 2022)
Abstract Objective Latino populations in the United States are disproportionately affected by substance use, HIV/AIDS, violence, and mental health issues (SAVAME). A growing body of evidence demonstrates the syndemic nature of SAVAME and the need for integrated strategies to reduce their impact. This study sought to understand the network of SAVAME services for Latino immigrants in Philadelphia to inform future interventions for SAVAME prevention and mitigation. Methodology Key informant interviews (N = 30) were conducted with providers working in Latino-serving organizations providing SAVAME services. Interviews were analyzed using thematic coding and grounded theory. Results Latino-serving providers perceived a large need for, and important limitations in the availability, accessibility, and adequacy of SAVAME services for Latino immigrants. Gaps were seen as especially acute for mental health and substance use services, partly because of insufficient funding for these services. Latino immigrants' lack of health insurance, immigration status, limited English proficiency (LEP), stigma surrounding SAVAME issues, and limited knowledge of available services were identified as significant barriers preventing access to services. Providers noted that scarcity of well-trained, culturally competent, and ethnically concordant providers reduced the adequacy of SAVAME services for Latino immigrant clients. The small size, low levels of infrastructure, and limited capacity were reported as additional factors limiting the ability of many Latino-serving organizations to adopt a syndemic approach in the prevention and treatment of SAVAME services. Conclusions The results call for changes in the structure of funding streams and communitywide strategies to foster collaboration across SAVAME providers working with Latino immigrant clients.